Novel characterisation methods for pore systems of seal rocks in reservoirs used for downhole gas production and storage - Pitcher, Eleanor Grace (2021)
Seal rocks, also called cap rocks, are a crucial and sometimes overlooked factor (due to not being the primary factor in exploration, having more of a role in the resource evaluation and development) in the evaluation of a potential gas accumulation, and is critical in downhole gasification (enhanced gas recovery) and storage of other gases. Shale rocks are the most common seal rock in conventional reservoirs; currently shales are providing an unconventional oil and gas source which can act as a potential buffer to the energy industry as it transitions towards renewable energies (which are still in their formative years) whilst there is a continued rise in demand for energy globally. Over the past ten years there has been a boom in shale gas production in the United States (Barsotti et al., 2016; Li et al., 2016; Yu et al., 2016), and it is anticipated that this boom may be repeated in the UK (Andrews, 2013).